Paradigma Dan Revolusi Ilmiah Thomas S. Kuhn Serta Relevansinya Dalam Ilmu-Ilmu Keislaman - Edi Kurniawan Farid (Universitas Darussalam Gontor, 2021)
The study of Thomas S. Kuhn's thought about the scientific revolution and its relevance to Islamic sciences is important. Although the Kuhn's thoughts of scientific revolution has fundamental and philosophical differences considering the historical aspects and the origin of its emergence which do have different characteristics, these adaptive and accommodative efforts in the history of Islamic scholarship have occurred. This study aims to describe how Thomas S. Kuhn's thought about the scientific revolution, its stages, and its relevance in Islamic science. This study is a literature study, where data is collected by using documentation technique and analyzed through the data reduction, data display, and concluding. The scientific revolution assumes that the development of science is drastic and revolutionary. The shifting paradigm from the old paradigm to the new one is what has led to a science developing radically. The stages include paradigm I, normal science, anomaly, crisis, scientific revolution, paradigm II. In this case the main key to the scientific revolution is methodology. So, in the context of the developing Islamic Sciences, the methodology of how understanding the Islamic teaching must be changed (revolutionized) according to the times, and not changing the Islamic teaching text itself. So that what happens is the dynamic of the Muslims paradigm towards religion which has been continuously carried out throughout the ages.